Self-regulation practices in Malaysian media / Syed Agil Shekh Alsagoff - Syed Agil , Shekh Alsagoff (2016)
The popularity of digital media and the availability of a seemingly borderless world of communication networks have formed a new environment which supported by the Information and Communication Technologies (ICT). Along with the Malaysian government’s Multimedia Super Corridor (MSC) projects, a National Communication and Multimedia Policy were introduced. This was to provide clear guidelines for the media industry behavior and encourage the development of self-regulatory mechanisms for local industry players while minimizing the costs of regulation. The implementation of voluntary codes of practice for the industry must be in line with the government’s policy objectives. This study identified how the self-regulatory mechanisms would benefit the industry and the future growth of media technologies in this country. This is for the industry to proactively respond to the winds of change breezing through media convergence technology policies and legislations on certain key issues faced by the Malaysian media environment. The thesis identifies an important relationship between the regulators, media industry and public interest upon the implementation of media self-regulation in Malaysia. The challenges faced by the government and media players regarding the broadcast of new media content had become a discourse for the both parties to implement best practices of self-regulatory mechanisms. These issues sanction the self-management of information dissemination in the name of public and industry interests, while in the same token ensure preservation of the national identity and cultures.